واقع وتحديات الهيئات البرلمانية والتشريعية في ظل جائحة كورونا: REALITY AND CHALLENGES OF PARLIAMENTARY AND LEGISLATIVE AUTHORITIES IN LIGHT OF CORONA VIRUS PANDEMIC (International Seminar on Syariah and Law (INSLA), 2020)
The legislative authorities' responses to the COVID-19 pandemic initially raised questions about whether and how parliaments and legislatures should continue to meet during the pandemic. By analyzing the parliamentary facts from all elected and appointed federal, regional, and international legislative bodies, we found that the role of councils and legislative bodies as sites for citizens' representation has suffered the most, while the scrutiny and legislative functions of parliaments tend to preserve the achievements of the peoples, albeit in a form of conservatism. We found that the characters in the responses of the various legislative bodies to the epidemic reveal aspects of the performance of these councils, which have given priority to enacting legislation that serves the interests of societies, indifferent to the risk of disease exposure to their members, so their goal was to serve the people, putting the interests of people above every consideration. Accordingly, in my research paper, I will review the efforts made by the parliamentary and legislative bodies to preserve their work in addition to their basic work, which is the voice of the people they represent and the pursuit of a comprehensive representation of their needs. في البداية أثارت ردود الهيئات التشريعية على جائحة فايروس كورونا كوفيد 19 أسئلة حول ما إذا كان ينبغي للبرلمانات والمجالس التشريعية أن تستمر في الاجتماع أثناء الوباء وكيف ينبغي ذلك. من خلال تحليل الوقائع البرلمانية من جميع الهيئات التشريعية الاتحادية والإقليمية والدولية المنتخبة والمعينة، وجدنا أن دور المجالس والهيئات التشريعية كمواقع لتمثيل المواطنين قد عانى أكثر من غيره، في حين أن وظائف التدقيق والتشريع للبرلمانات تميل إلى الحفاظ على منجزات الشعوب، وإن كان ذلك في تحفظ بشكل كبير. وجدنا بأن الصنوف في استجابات الهيئات التشريعية المتنوعة للوباء تكشف عن جوانب الأداء لهذه المجالس التي أعطت الأولوية لسن تشريعات تخدم مصالح المجتمعات غير مبالية بما تعرض لها أعضاءها من خطر الإصابة بالمرض، فكان هدفهم خدمة الشعوب واضعين مصالح البشر فوق كل اعتبار. وعليه، سوف استعرض في ورقتي البحثية هذه، الجهود التي قامت بها الهيئات البرلمانية والتشريعية، للمحافظة على اعمالها بالإضافة الى عملهم الأساسي، وهو صوت الشعب الذي يمثلونه والسعي الى التمثيل الشامل لمتطلباتهم.